An extramedullary plasmacytoma in the testicle: A case report and review of the literature - Lue, Kathy; Emtage, Justin B; Pariñas, Maria Ana; Dhillon, Jasreman; Pow-Sang, Julio (Canadian Urological Association Journal, 2015)
We present a rare case of testicular extramedullary plasmacytoma (EMP) in a 43-year-old man with multiple myeloma and diffuse systemic involvement refractory to chemotherapy. Multiple myeloma is typically found within the bone marrow and rarely involves other organs and sites. EMPs are most frequently associated with the head and neck region, but in rare cases testicular involvement have been seen. These mimic other causes of testicular swelling and therefore require a full diagnostic workup and management similar to that of any scrotal pathology. Radical inguinal orchiectomy is the treatment of choice with the addition of adjunct or salvage radiation therapy if necessary. The prognosis with these lesions is poor and in cases of primary testicular plasmacytoma, progression to multiple myeloma is likely.